Effects of flaxseed (Linum usitatissimum) extract on osteoblast differentiation potential of stem cells derived from human exfoliated deciduous teeth (SHED) - Nordin, Nur Sazwi; Mokhtar@Makhtar, Khairani Idah; Mustafa Al-Ahmad, Basma Ezzat; Lestari, Widya; Arief Ichwan, Solachuddin Jauhari; Darnis, Deny Susanti; Thirumulu Ponnuraj, Kannan; Ahmad, Azlina (2019)
Introduction: Flaxseed extract promotes bone health and possibly function in inducing bone regeneration process. SHED have been considered as an alternative source of MSC in tissue engineering because of their potential to differentiate into multiple cell-lineages including osteoblasts. Although flaxseed extract has been shown to affect bone formation process, its effect in inducing stem cell into osteoblast lineage has not been reported. Objective: To determine the effects of flaxseed extract on osteoblast differentiation potential of SHED. Materials and methods: SHED cultured in osteoblast induction media (OIM) was treated with flaxseed extract at 4mg/ml. The RNA was collected and extracted with Total RNA Mini Kit (Geneaid) from cells cultured at day 1, 3, 7, 14 and 21 and subjected to reverse-transcriptase PCR for osteoblast markers (OSX, OCN, DMP1). Alkaline phosphatase activity was determined by ALP assay and Alizarin Red S staining was performed to evaluate calcium deposits in SHED. Results: All osteoblast markers were expressed in all samples analysed. Interestingly, the expression of OSX appeared to be reduced in SHED treated with flaxseed extract. In addition, SHED treated with flaxseed extract resulted in low ALP activity compared to control (p<0.05) (t-test). Calcium deposition was positive in SHED cultured in OIM only. Conclusion: Flaxseed appears to reduce the expression of osteoblast markers, ALP activity and calcium deposition in SHED. This suggests that flaxseed as a potential inhibitor in osteoblast differentiation of SHED.